Studi Disiplin Kerja, Kompetensi dan Kompensasi Terhadap Kinerja Karyawan - Hendy Halim; Hendry Hendry; Jonathan Intan; Celvin Alexander; Mellisa Amanda Wirani Putri; Lastari Lastari (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of work discipline, competence and compensation on employee performance. The method used in this study is to use descriptive methods and associative methods. Population and sample in this study amounted to 52 employees of data collection techniques conducted by researchers in this study is through observation, questionnaire interviews, documentation and literature studies. Data analysis techniques starting from the preparation of data, data tabulation to the testing phase. Based on the results of the calculation of the t test and F test obtained work discipline, competence and compensation have a positive and significant effect on employee performance. The value of the coefficient of determination (R2) can be obtained from the variabel of work discipline, competence and compensation affect 38.8% (0.388) on employee performance, the remaining 61.2% influenced by other factors outside this study. Conclusion, work discipline, competence and compensation impact on employee performance. Keywords: Work Discipline, Competence, Compensation, Employee Performance.